2016
DOI: 10.5194/acp-16-14795-2016
|View full text |Cite
|
Sign up to set email alerts
|

Regional and local variations in atmospheric aerosols using ground-based sun photometry during Distributed Regional Aerosol Gridded Observation Networks (DRAGON) in 2012

Abstract: Abstract. Aerosol mass concentrations are affected by local emissions as well as long-range transboundary (LRT) aerosols. This work investigates regional and local variations of aerosols based on Distributed Regional Aerosol Gridded Observation Networks (DRAGON). We constructed DRAGON-Japan and DRAGON-Osaka in spring of 2012. The former network covers almost all of Japan in order to obtain aerosol information in regional scale over Japanese islands. It was determined from the DRAGON-Japan campaign that the val… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Osaka is a megacity of very dense urban development that is bounded by low mountains on three sides and Osaka Bay to the south (see Sano et al, 2016). Industry and transportation emissions are sources of the dominant background aerosol loading, and, as in Seoul, episodic coarsemode dust and transported fine-mode industrial aerosols were observed during the 4-month intensive measurement period.…”
Section: Dragon-japanmentioning
confidence: 99%
See 1 more Smart Citation
“…Osaka is a megacity of very dense urban development that is bounded by low mountains on three sides and Osaka Bay to the south (see Sano et al, 2016). Industry and transportation emissions are sources of the dominant background aerosol loading, and, as in Seoul, episodic coarsemode dust and transported fine-mode industrial aerosols were observed during the 4-month intensive measurement period.…”
Section: Dragon-japanmentioning
confidence: 99%
“…The long-range trans-boundary aerosols during this period were shown to follow the NCEPderived 700 to 850 mb wind vectors. Sano et al (2016) investigated the variability in AOD under clean and polluted days in Osaka using DRAGON network measurements. They also detailed aerosol transportation over the city using high spatial-and temporal-resolution measurements by DRAGON-Osaka.…”
Section: Observations Of Aerosols Above Clouds and Their Interactionsmentioning
confidence: 99%
“…They analyzed the spatial representativeness of individual AERONET sites and found that this depends on the season and the dominant aerosol type. Lee and Son (2016) and Sano et al (2016) studied the variability of AERONET aerosol optical properties during the DRAGON-Asia campaign in 2012. Sano et al (2016) concluded that due to the high variability in AOD, the ground-based measurements should be more frequent, and the satellite retrievals should have a finer resolution for a proper comparison.…”
Section: T H Virtanen Et Al: Collocation Mismatch Uncertaintiesmentioning
confidence: 99%
“…Lee and Son (2016) and Sano et al (2016) studied the variability of AERONET aerosol optical properties during the DRAGON-Asia campaign in 2012. Sano et al (2016) concluded that due to the high variability in AOD, the ground-based measurements should be more frequent, and the satellite retrievals should have a finer resolution for a proper comparison. Xiao et al (2016) compared AOD retrievals from several satellites to data from the DRAGON-Asia campaign and handheld sun photometers and concluded that the satellite products are better at tracking the day-to-day variability than tracking the spatial variability.…”
Section: T H Virtanen Et Al: Collocation Mismatch Uncertaintiesmentioning
confidence: 99%
“…They analyzed the spatial representativeness of individual AERONET sites, and found that this depends on the season 5 and the dominant aerosol type. Lee and Son (2016) and Sano et al (2016) studied the variability of AERONET aerosol optical properties during the DRAGON-Asia campaign in 2012. Sano et al (2016) concluded that due to the high variability in AOD, the ground based measurements should be more frequent, and the satellite retrievals should have a finer resolution for a proper comparison.…”
mentioning
confidence: 99%